2015 IEEE 15th International Conference on Environment and Electrical Engineering (EEEIC) 2015
DOI: 10.1109/eeeic.2015.7165276
|View full text |Cite
|
Sign up to set email alerts
|

A control strategy of hybrid system “diesel-photovoltaic-battery” for stand-alone applications

Abstract: this paper describes a control strategy of a dieselsolar-battery hybrid system for standalone applications. the PV generator and batteries are primary sources of energy in the system; diesel generator is interconnected to the AC bus, when approached it can supply power load and charges batteries simultaneously ; as it can supply part of power load in parallel with the PV generator and batteries. In this context, the DC / AC converter that connects the DC bus to AC bus is synchronized with the diesel generator;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Two classical models, the 'synchronverter' and Ise's, focus on the loss of inertia in conventional VSI droop control, and the emulation of the properties of the inertia and the speed-governor is implemented [9,11,13]. Experiment-based studies can be found in [14,15] for stand-alone applications. In [12], the equivalence between the VSG and the frequency-droop algorithms are demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Two classical models, the 'synchronverter' and Ise's, focus on the loss of inertia in conventional VSI droop control, and the emulation of the properties of the inertia and the speed-governor is implemented [9,11,13]. Experiment-based studies can be found in [14,15] for stand-alone applications. In [12], the equivalence between the VSG and the frequency-droop algorithms are demonstrated.…”
Section: Introductionmentioning
confidence: 99%